2015
DOI: 10.1080/10494820.2015.1041398
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of employing Google Docs in collaborative concept mapping on achievement, concept representation, and attitudes

Abstract: This study investigated the effectiveness of using Google Docs in collaborative concept mapping (CCM) by comparing it with a paper-and-pencil approach. A quasiexperimental study was conducted in a physics course. The control group drew concept maps using the paper-and-pencil method and face-to-face discussion, whereas the experimental group employed Google Docs to create concept maps and used Google Chat for discussion. Learning achievements, physics concept representation, attitudes toward science, and attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 67 publications
2
49
0
3
Order By: Relevance
“…Previous studies have reported that collaborative mind-mapping can be used to promote scientific knowledge discourse by co-creation of knowledge in research teams and mutual negotiation of relationships on mind-maps. Previous research has also discovered that having a collaborative visualization of ideas can facilitate co-construction of knowledge and discussion in these types of visualizations are more rich and facilitate a higher level of collaboration among participants [1,3]. Another issue with regards to cloud-based collaborative mind-mapping is most of the tools are unable to provide real-time collaborative mind-mapping.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported that collaborative mind-mapping can be used to promote scientific knowledge discourse by co-creation of knowledge in research teams and mutual negotiation of relationships on mind-maps. Previous research has also discovered that having a collaborative visualization of ideas can facilitate co-construction of knowledge and discussion in these types of visualizations are more rich and facilitate a higher level of collaboration among participants [1,3]. Another issue with regards to cloud-based collaborative mind-mapping is most of the tools are unable to provide real-time collaborative mind-mapping.…”
Section: Introductionmentioning
confidence: 99%
“…The software used allowed collaborative mind-mapping to be carried out in both synchronous and asynchronous manner, which allowed for real-time collaboration and interaction [1]. Furthermore, the tool allowed for tracking of the mind-mapping process in which it allowed maps to be re-visited to an earlier version [2].…”
Section: A Real-time Cloud-based Collaboration Toolmentioning
confidence: 99%
See 3 more Smart Citations